A Neutral Gas Mass Spectrometer to Measure the Chemical Composition of the Stratosphere ... - Abplanalp, Dominic; Wurz, Peter; Wieser, M.; Barabasch, M. (University of Bern, 2010)
The Polar Balloon Atmospheric Composition Experiment (P-BACE) is a new generation of neutral gas mass spectrometer based on the time-of-flight principle. P-BACE is the only scientific experiment on the Mars Environment Analogue Platform (MEAP) flown successfully on a balloon mission in summer 2008. The MEAP mission was flown with a 334,000 m3helium balloon in the stratosphere on a semicircular trajectory from northern Sweden around the North Pole to Canada. The atmospheric conditions at an atmospheric altitude of 35 – 40 km are remarkably similar to those on the surface of Mars and thus the balloon mission was an ideal testbed for our mass spectrometer P-BACE. Originally this instrument was designed for in situ measurements of the chemical composition of the Martian atmosphere. The balloon mission lasted five days and had successfully demonstrated the functionality of the P-BACE instrument during flight conditions. We had recorded more than 4,500 mass spectra. ...